IS/IT Benefits Realisation and Management in Large Australian Organisations - Pervan, Graham; Lin, Chad (School of Information Systems, Curtin Business School, Curtin University of Technology, 2000)
Information systems and technology investments in organisations are substantial and growing. While formal methodologies and techniques for evaluating these investments are used to some extent, relatively less formality is applied to managing and realising their benefits. Part of an ongoing research programme, this study examines a number of aspects of IS/IT benefits realisation in large Australian organisations and reveals issues of identifying and structuring benefits, planning benefits realisation, delivering, evaluating and reviewing these benefits, with some success and some failure. The results show some use of formal methodologies, benefits measurement, formal reviews, and allocation of specific responsibilities, but a lack of uniformity in the formality of the activities. These results, however, are generally consistent with findings in related studies outside Australia.